Potential platinum DNA-Metallointercalators : synthesis, characterisation and 1H NMR studies on [Pt(diimine)(N,N-di(n-butyl)-N'-acylthioureato)]+PF6 complexes in solution - Lawrence, Claire Joanna (Department of Chemistry, 2016)
Summary in English.